Effect of a novel prime‐and‐rinse approach on short‐ and long‐term dentin bond strength of self‐etch adhesives. (31st October 2019) - Li, Mingxing; Xu, Jingqiu; Zhang, Ling; Wang, Chaoyang; Jin, Xiaoting; Hong, Yan; Fu, Baiping; Hannig, Matthias
Abstract : This study investigated the effects of the prime‐and‐rinse approach, using a 10‐methacryloyloxydecyl dihydrogen phosphate (MDP)‐containing primer, on the short‐ and long‐term dentin microtensile bond strengths (MTBSs) of mild self‐etch adhesives. Half of sixty human midcoronal dentin surfaces were polished as control (self‐etch approach), and the other half were polished and further treated with a 15% MDP‐containing primer and thoroughly sprayed with water as prime‐and‐rinse approach. The dentin surfaces were treated with a self‐etch adhesive, and a composite resin was placed on the surfaces. The following materials were used: Clearfil S3 Bond+Clearfil Majesty; G‐Bond+Gradia Direct; Adper Easy One+Z250; and i Bond+Charisma. The MTBS was examined after 24 h and 14 months in water storage. The resin–dentin interfaces were analysed using scanning electron microscopy/transmission electron microscopy. Pretreated dentin surfaces were further analysed using scanning electron microscopy and micro‐Raman spectroscopy. Compared with the self‐etch approach, the prime‐and‐rinse approach significantly increased the dentin MTBS, regardless of the duration of storage. The scanning electron microscopy/transmission electron microscopy findings revealed that the prime‐and‐rinse approach removed most of the dentin smear layer. The Raman spectra of the MDP‐treated dentin reveal the characteristic spectra of collagen, hydroxyapatite, and the monomer. Therefore, the prime‐and‐rinse approach using MDP‐containing primers prior to the application of mild self‐etch adhesives significantly increases the short‐ and long‐term MTBS of dentin.